2018
DOI: 10.1021/acsmedchemlett.8b00283
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of an Indazole-Based Selective Protein Arginine Deiminase 4 (PAD4) Inhibitor

Abstract: Protein arginine deiminase 4 (PAD4) is a calcium-dependent enzyme that catalyzes the conversion of arginine to citrulline within target proteins. Dysregulation of PAD4 has been implicated in a number of human diseases, including rheumatoid arthritis and other inflammatory diseases as well as cancer. In this study, we report on the design, synthesis, and evaluation of a new class of haloacetamidine-based compounds as potential PAD4 inhibitors. Specifically, we describe the identification of 4,5,6-trichloroindaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Ellman et al [ 101 ] prepared and evaluated a novel series of N -alkylated indazole chloroacetamidine derivatives as potential protein arginine deiminase 4 (PAD4) inhibitors. Derivatization around the indazole ring with chloro substituents then led to the identification of trichloroindazole compound 173 with high inhibitory activity against PDAs ( k inact / K I values: PDA1, 20 ± 5; PAD2, 940 ± 240; PAD3, 5100 ± 400, 5,4000 ± 3000) ( Figure 54 ).…”
Section: Biological Applications Of Indazole Derivativesmentioning
confidence: 99%
“…Ellman et al [ 101 ] prepared and evaluated a novel series of N -alkylated indazole chloroacetamidine derivatives as potential protein arginine deiminase 4 (PAD4) inhibitors. Derivatization around the indazole ring with chloro substituents then led to the identification of trichloroindazole compound 173 with high inhibitory activity against PDAs ( k inact / K I values: PDA1, 20 ± 5; PAD2, 940 ± 240; PAD3, 5100 ± 400, 5,4000 ± 3000) ( Figure 54 ).…”
Section: Biological Applications Of Indazole Derivativesmentioning
confidence: 99%
“…11,12 Moreover, PAD4 inhibitors have been considered as potential targets for cancer treatment. [13][14][15][16][17] A recent study demonstrates that PAD4specific inhibitor GSK484 could alleviate myocardial infarction triggered cardiac dysfunction. 18 In our research, we found that GSK484 sensitized MDA-MB-231 and BT-549 cells to ionizing radiation by enhancing the inhibition of post-irradiation cell proliferation, migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…12 Moreover, recent studies have demonstrated that PAD4 inhibitor may provide a novel insight for the treatment of cancers. [13][14][15][16] Compared with methotrexate-alone treatment, the combination of PAD inhibitor and methotrexate treatment increased the cytotoxic effect on prostate cancer cells. 17 As a newly discovered PAD4 inhibitor, GSK484 has been found to moderately alleviate cardiac dysfunction induced by myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%
“…2H-Indazole is one such heterocylic compound, which has been extensively utilized for numerous biological applications. [19][20][21][22] Indazoles are often isosteric with other classes of synthetically important 1,2-azoles. [23] Diversely substituted 2H-indazole compounds with variously substituted functional groups, possess a wide spectrum of pharmacological activities and also serve as scaffolds for many drug molecules.…”
Section: Introductionmentioning
confidence: 99%
“…2 H ‐Indazole is one such heterocylic compound, which has been extensively utilized for numerous biological applications . Indazoles are often isosteric with other classes of synthetically important 1,2‐azoles .…”
Section: Introductionmentioning
confidence: 99%